Combining Seed Dressing and Foliar Applications of Phosphorus Fertilizer Can Give Similar Crop Growth and Yield Benefits to Soil Applications Together With Greater Recovery Rates - Talboys, Peter J.; Healey, John R.; Withers, Paul J. A.; Roose, Tiina; Edwards, Anthony C.; Pavinato, Paulo S.; Jones, Davey L. (Frontiers in Agronomy, 2020)
Phosphorus (P) fertilisers have a dramatic effect on agricultural productivity, but conventional methods of application result in only limited recovery of the applied P. Given the increasing volatility in rock phosphate prices, more efficient strategies for P fertiliser use would be of economic and environmental benefit in the drive for sustainable intensification. This study used a combination of controlled-environment experiments and radioisotopic labelling to investigate the fertiliser use efficiency of a combination of seed (grain) dressing and foliar applications of P to spring wheat (Triticum aestivum L.). Radioisotopic labelling showed that the application of foliar P in the presence of photosynthetic light substantially increased both P-uptake into the leaf and P-mobilisation within the plant, especially when an adjuvant was used. When compared with soil application of inorganic P buried into the rooting zone, a combination of 3 µmol seed dressings and three 46.3 µmol plant-1 foliar applications were far more efficient at providing P fertilisation benefits in P-limiting conditions. We conclude that a combination of seed dressing and foliar applications of P is potentially a better alternative to conventional soil-based application, offering greater efficiency in use of applied P both in terms of P-uptake rate and grain yield. Further work is required to evaluate whether these results can be obtained under a range of field conditions.